Class, Habitus, and the Dynamics of Social Relations of Traders in Diamond Trade in the Martapura Town, South Kalimantan - Yusuf Hidayat (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
This study examines the pattern of social relationships among diamond traders in diamond trade that polarized into patterns of social relationships between small, medium and large traders with their respective values. This study aims to describe the pattern of social relationships between diamond traders and reveal the rules of the underlying game patterns of their social relationships that lead to polarization of social relationships between small, medium and large traders. This study used Buordieu framework especially about Field, Habitus, and Doxa to analyze the phenomena. This research uses qualitative research methods and has been implemented in the town of Martapura, South Kalimantan. In this study, five people were interviewed, consisting of merchants of a large trader, two medium traders and two merchants. The study finds that first, there are three forms of social relations pattern among traders of diamond namely: cooperation relationships between small traders, competition relationships between wholesalers and middle traders in accordance with its position, he develops cooperative relationships while in diamond market and relationships competition when trading outside the diamond market. Second, Each class has its own rules of play in accordance with their capacity in the sale and purchase of diamonds and the rules of this game have become a common consciousness among members of the merchant class so that all members of the group implement these rules spontaneously and without questioning its validity.